1990
DOI: 10.1021/ac00223a016
|View full text |Cite
|
Sign up to set email alerts
|

Glucose fast-response amperometric sensor based on glucose oxidase immobilized in an electropolymerized poly(o-phenylenediamine) film

Abstract: o-Phenylenediamine has been used for glucose oxidase (GOx) immobilization on Pt electrodes by electrochemical polymerization at +0.65 V vs SCE. By this approach the enzyme is entrapped in a strongly adherent, highly reproducible thin membrane, whose thickness is around 10 nm. This one-step procedure produces a glucose sensor with a response time less than 1 s, an active enzyme loading higher than 3 units/cm2 of electrode surface, a high sensitivity, and a sufficiently wide linear range. The glucose response sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
334
5
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 555 publications
(358 citation statements)
references
References 45 publications
17
334
5
2
Order By: Relevance
“…2), i.e., similar to Pt/PPD/GOx electrodes [33][34][35][36][37][38][39] but much faster than sensors incorporating PEA by the drop coating technique. 45 The sensitivity was high in the linear range (0-100 mmol l 21 Glu, 3.8 ± 1.3 nA cm 22 mmol 21 l, r 2 = 0.99 ± 0.01, n = 4) with a low LOD (2 3 s of baseline, see Table 1).…”
Section: Other Characteristics Of the Pt/pea/ppd/bsa/gluox Sensormentioning
confidence: 97%
See 1 more Smart Citation
“…2), i.e., similar to Pt/PPD/GOx electrodes [33][34][35][36][37][38][39] but much faster than sensors incorporating PEA by the drop coating technique. 45 The sensitivity was high in the linear range (0-100 mmol l 21 Glu, 3.8 ± 1.3 nA cm 22 mmol 21 l, r 2 = 0.99 ± 0.01, n = 4) with a low LOD (2 3 s of baseline, see Table 1).…”
Section: Other Characteristics Of the Pt/pea/ppd/bsa/gluox Sensormentioning
confidence: 97%
“…17,24 The classical procedure for incorporating oxidase enzymes into a protecting polymer film has been to co-deposit the enzyme and polymer onto the electrode from a solution of the enzyme and monomer. [33][34][35][36][37][38][39] This is convenient and effective but is very cost-inefficient for expensive enzymes such as GluOx. The aim of this work was to develop a more efficient procedure for producing Pt/ PPD/GluOx sensors with high sensitivity to Glu.…”
mentioning
confidence: 99%
“…Pt F /PEI/GluOx/PPD biosensors, incorporating the enzyme GluOx and sensitivity-boosting polycation PEI, 31,42,46,96 were therefore fabricated and calibrated in vitro for Glu, H 2 O 2 , and AA. The sensitivity to Glu in the linear response region of the Michaelis-Menten calibration curve was high (62 ± 8 µA cm -2 mM -1 , n ) 14), representing 24 ± 4% of the sensitivity of the same biosensors in H 2 O 2 calibrations performed under the same quiescent conditions, and reflecting efficient enzyme kinetics in these ultrathin insulating PPD coatings (<30 nm [56][57][58][59][60] 14%, n ) 14) and P(AA)% (0.20 ± 0.04%, n ) 14) indicate that the dip-evaporation deposition of both PEI and GluOx on the bare Pt F before PPD electrosynthesis only marginally affected the ability of the composite polymer matrix to reject AA interference or to enable efficient H 2 O 2 transport to the metal surface. Not surprisingly, as a result of incorporating these two macromolecular species into the PPD matrix, its permeability increased, but by only a factor of 2 for both parameters (see Figures 4 and 5), minimizing the effects on selectivity.…”
Section: P(aa)% Analysis For Ppd-modified Electrodesmentioning
confidence: 99%
“…Recently, the groups of Zambonin (Malitesta et al, 1990) and Yacynych (Sasso et al, 1990) have reported H 2 O 2 -detecting biosensors based on the immobilisation of GOx in electropolymerized poly(phenylenediamine) films on Pt electrodes with properties (e.g. interferencefree, high enzyme activity and low response time) indicating ideal suitability for detecting substrates in biological fluids.…”
Section: Introductionmentioning
confidence: 99%